2006
DOI: 10.1107/s0907444906012601
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization to obtain protein–ligand complexes for structure-aided drug design

Abstract: Danley Structure-aided drug design 571 feature articles Acta Cryst. (2006). D62, 569-575 Danley Structure-aided drug design 573 feature articles Acta Cryst. (2006). D62, 569-575 Danley Structure-aided drug design 575

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…Use of X-ray crystallography-derived 3D structures for structure-aided drug design is a common activity in drug discovery today (14). In this process, the structures of macromolecular targets, often proteins or protein complexes complexed with their natural ligands or identified inhibitors, are solved and the structural information is used to design inhibitors or screen molecules for putative inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Use of X-ray crystallography-derived 3D structures for structure-aided drug design is a common activity in drug discovery today (14). In this process, the structures of macromolecular targets, often proteins or protein complexes complexed with their natural ligands or identified inhibitors, are solved and the structural information is used to design inhibitors or screen molecules for putative inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…[15] It has also been reported that structures of ligand-binding proteins can be employed in computational protein engineering to generate mutants with artificial functions. [16] Therefore, the inhibitors described here will contribute to our efforts to generate a ligand library that could be used to enhance PhaC crystallization for its first structure.…”
Section: Introductionmentioning
confidence: 99%
“…For 90% occupancy, the amount of added ligands must be greater than the amount of protein so that free ligands at equilibrium is not depleted to less than about 10 × K d . 30 In practice, ratios of ligands to a given protein up to 10:1 or more are commonly used, but large excesses should be avoided owing to the possibility of ligand binding to nonspecific sites. In the case of a weak binding affinity, the concentrations of ligands (or ligand solubility) may have to be 10 mM or higher in order to observe crystallographic occupancy.…”
Section: Crystallization and Diffraction Of Lg-vitamin D 3 Complex Prmentioning
confidence: 99%
“…For 90% occupancy, the amount of added ligands must be greater than the amount of protein so that the free ligands at equilibrium are not depleted. 30 In this work, we reported a rationally designed approach for preparing the complex of LG and vitamin D 3 at various pH and vitamin D 3 /LG ratios to optimize the occupancy of vitamin D 3 and improve the electron density of the secondary binding site. Finally, we identified an exosite for vitamin D binding to be located near the R-helix and -strand I of LG using a crystal prepared at pH 8 with a vitamin D 3 /LG ratio of 3:1.…”
Section: Introductionmentioning
confidence: 99%